Inner form of noun morphological derivatives with different derivational meanings in Russian language - Kovaleva, Anna I. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to the problem of relation between types of derivational meaning (mutation, modification, transposition) of Russian derivated nouns and inner form dimension. The groups of nouns with modification and transposition derivational meaning the inner form of which are not words motivating them are distinguished. The article clarifies the question of correlation between motivation and inner form of derivatives. It demonstrates that the inner form of derivatives following each other in derivational string could be the same. Non-fixed position of inner form of a word in derivational family is emphasized.